Chapter 5.9 Maturity in the Professionalisation of the Research Managers and Administrators in Colombia - Salim Chalela Naffah; Andrea Navas Calixo (Emerald Publishing Limited, 2023)
This chapter presents a narrative description of the evolution in the building capabilities in the process of professionalisation of the research manager and administrative roles in higher education institutions (HEIs) in Colombia. The descriptive approach takes into account the consolidation of the Colombian Science, Technology and Innovation policy to explain the ways that research managers have been setting up their activities to adapt and respond to the challenges that research management has imposed on them. The chapter also includes analysis of results derived from the Research Administration as Profession (RAAAP-3) survey in 2022 for Colombian participants to describe as the roles of research managers and administrators that have grown up in the country, and it considers the future and perspectives to look forward in the professionalisation process in HEIs.
10.1108/978-1-80382-701-820231042; 10.1108/978-1-80382-701-820231042; The Emerald Handbook of Research Management and Administration Around the World; EBP099697262